2014
DOI: 10.1161/circulationaha.113.008364
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Fibroblast Glycogen Synthase Kinase-3β Regulates Ventricular Remodeling and Dysfunction in Ischemic Heart

Abstract: Background Myocardial infarction-induced remodeling includes chamber dilatation, contractile dysfunction, and fibrosis. Of these, fibrosis is the least understood. Following MI, activated cardiac fibroblasts (CFs) deposit extracellular matrix. Current therapies to prevent fibrosis are inadequate and new molecular targets are needed. Methods and Results Herein we report that GSK-3β is phosphorylated (inhibited) in fibrotic tissues from ischemic human and mouse heart. Using two fibroblast-specific GSK-3β knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
173
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(184 citation statements)
references
References 34 publications
4
173
2
1
Order By: Relevance
“…We showed that there was significantly attenuated cardiac fibrosis in infarcted groups treated with LiCl, SB216763, and the combination of LiCl and SB216763 compared with vehicle. This result contrasted with the findings of Lal et al, 45 showing an increase in the fibrotic response in cardiac fibroblast-conditioned GSK-3b knockout mice after MI. This discrepancy can be explained at least in part, by different affected cells, different levels of GSK-3 inhibition, and different GSK-3 isoforms.…”
Section: Previous Studiescontrasting
confidence: 99%
“…We showed that there was significantly attenuated cardiac fibrosis in infarcted groups treated with LiCl, SB216763, and the combination of LiCl and SB216763 compared with vehicle. This result contrasted with the findings of Lal et al, 45 showing an increase in the fibrotic response in cardiac fibroblast-conditioned GSK-3b knockout mice after MI. This discrepancy can be explained at least in part, by different affected cells, different levels of GSK-3 inhibition, and different GSK-3 isoforms.…”
Section: Previous Studiescontrasting
confidence: 99%
“…Ischemia-associated FBs have a critical influence on myocardial remodeling progression and fibrosis. [1][2][3] Myocardial remodeling is the product of interactions between FBs and adjacent cells, such as CMs, and blood vascular endothelial cells (ECs), although the exact mechanisms remain poorly understood. 4,5 Pleiotropic effects of cardiac FBs are mediated through differentiation to a myofibroblast phenotype and secretion of pro-inflammatory cytokines (eg, IL-6, TGF β, TNFα, and IL-1).…”
mentioning
confidence: 99%
“…Fibroblast-specific periostin promoter-driven Cre (Postn-Cre) transgenic mice (mixed background) were provided by Simon J. Conway (Indiana University School of Medicine, Indianapolis, Indiana, USA). Cre recombinase was driven by a 3.9-kb mouse Postn promoter (44)(45)(46). To obtain a fibroblast-specific deletion of the Rock2 gene, (A and B) Representative fluorescent images and quantification of cellular hypertrophy of H9C2 cells stained with sarcomeric α-actinin (green) and DAPI (nuclei, blue).…”
Section: Generation Of Fibroblast-specific Rock2-deficient Mice Condmentioning
confidence: 99%